School and community : the communitarian agenda in education - Arthur, James (Routledge Falmer, 2000)
Communitarianism, as a movement, is clearly a dominant theme within New Labour's educational policy. How does this affect education and the life and work of schools?Research has shown that there is a correlation between academic achievement and the strength of community life and awareness within a school. The aim of this book, therefore, is to introduce communitarian thought to classroom teachers and to those working in education. The book contextualizes the current debates within education around the many topical ideas being developed by communitarian thinkers, including:character bui.